The Influence of Intellectual Capital on Islamic Banks Profitability: A Mediation Analysis of Non-Profitability Performance and Islamicity Financial Performance Index - Rara Genta Munggarani Basri; Rahmat Mulyana; Hendri Tanjung (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. This study aims to analyze the influence of intellectual capital on Islamic banks' profitability in Indonesia, mediated by non-profitability performance and Islamicity Financial Performance Index variables. This study uses Structural Equation Modeling (SEM) analysis of secondary data from a sample of 8 (eight) Islamic commercial banks in the form of financial statements for 2018-2020. This research shows, first, intellectual capital directly has a significant positive influence on the Islamic banks' profitability in Indonesia. Second, intellectual capital mediated by non-profitability performance has a significant positive influence on Islamic banks’ profitability. Also, the relationship of intellectual capital through the Islamicity Financial Performance Index has a positive significant influence on the Islamic banks’ profitability. This indicates that intellectual capital gives new strength for Islamic banks to compete with conventional banks.Keywords: Intellectual Capital, Profitability, Non-Profitability Performance, Islamicity Financial Performance Index Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh intellectual capital terhadap profitabilitas bank umum syariah di Indonesia yang dimediasi oleh variabel kinerja non profitabilitas dan Islamicity Financial Performance Index. Penelitian ini menggunakan analisis Structural Equation Modelling (SEM) terhadap data sekunder dari sampel 8 (delapan) bank umum syariah berupa laporan keuangan tahun 2018-2020. Temuan pertama menunjukkan bahwa intellectual capital memiliki pengaruh yang positif secara signifikan terhadap profitabilitas bank syariah di Indonesia. Kedua, intellectual capital yang dimediasi oleh variabel kinerja non profitabilitas menghasilkan pengaruh yang positif secara signifikan terhadap profitabilitas bank syariah. Dan hubungan intellectual capital melalui Islamicity Financial Performance Index juga menghasilkan pengaruh yang positif secara signifikan terhadap profitabilitas bank syariah. Hal ini mengindikasikan bahwa intellectual capital memberikan kekuatan baru bagi bank syariah untuk bersaing dengan bank konvesional.Kata kunci: Intellectual Capital, Profitabilitas, Kinerja Non-Profitabilitas, Islamicity Financial Performance Index